2016
DOI: 10.1080/17470218.2015.1112825
|View full text |Cite
|
Sign up to set email alerts
|

Speech segmentation by statistical learning is supported by domain-general processes within working memory

Abstract: The purpose of this study was to examine the extent to which working memory resources are recruited during statistical learning (SL). Participants were asked to identify novel words in an artificial speech stream where the transitional probabilities between syllables provided the only segmentation cue. Experiments 1 and 2 demonstrated that segmentation performance improved when the speech rate was slowed down, suggesting that SL is supported by some form of active processing or maintenance mechanism that opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 27 publications
0
41
4
Order By: Relevance
“…This finding contrasts with results from Palmer and Mattys (2016), which showed improvements in segmentation when the speech stream was slowed. A plausible explanation for this inconsistency is that listeners may only be able to take advantage of slower speech under clear, unencumbered listening conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding contrasts with results from Palmer and Mattys (2016), which showed improvements in segmentation when the speech stream was slowed. A plausible explanation for this inconsistency is that listeners may only be able to take advantage of slower speech under clear, unencumbered listening conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent work by Palmer and Mattys (2016) demonstrated that slower syllable rates improved performance on a segmentation task in adults, even when they controlled for the total duration of the speech stream. They showed that adults who were familiarised to an artificial language at a slow rate (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Working memory resources are helpful during the consolidation of these templates (Cunillera et al, 2009; Lopez-Barroso et al, 2011). Recent research also suggests that SL is supported by working memory process which may include attentional refreshing or working memory update (Palmer and Mattys, 2016). Due to consolidation of the three-tone templates, tones within a triplet are easy to predict while the first tone of the triplet continues to be unpredictable resulting in a strong triplet onset effect.…”
Section: Discussionmentioning
confidence: 99%
“…[64]), or, relatedly, unsupervised versus supervised learning settings (see [65] for a discussion of the role of feedback in perceptual category learning). An additional factor that was shown to affect SL performance is the rate of presentation-with opposite effects of both the inter stimulus interval and the actual stimulus duration on SL performance in the visual versus auditory modality ( [35,36]; but see [66]). Whether rate of presentation constitutes a separate facet, or simply affects peripheral aspects to SL such as the encoding of individual elements, with different constraints in different modalities (see [11]), deserves further investigation.…”
Section: (A) Modality Specificitymentioning
confidence: 99%